P28 Chronic thromboembolic pulmonary hypertension: long term outcomes in surgical and non-surgical patients. (15th November 2016) - Quadery, SR; Condliffe, RA; Billings, C; Thompson, R; Elliot, CA; Charalampopolous, A; Hurdman, J; Hamilton, N; Armstrong, I; Sephton, P; Sabroe, I; Swift, A; et al.
Abstract : Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is commonly associated with a history of venous thromboembolism. Pulmonary endarterectomy (PEA) offers a potential cure in surgically accessible disease. However, a significant proportion of patients with CTEPH may not undergo surgery due to various reasons including disease distribution, comorbidities and patient choice This group of patients have previously been considered to have a poor outcome although an international registry has recently reported on improved medium term outcomes in this patient population. Aims and objectives: To compare long term survival of patients with CTEPH undergoing pulmonary endarterectomy (CTEPH-surgical-operated), surgically accessible disease not undergoing pulmonary endarterectomy (CTEPH-surgical-not-operated), surgically inaccessible disease (CTEPH-non-surgical). Methods: Data was retrieved from hospital records and departmental database for consecutive, treatment-naïve patients with CTEPH diagnosed between 1st January 2001 and 30th November 2014 and followed up till 30th November 2015 at the Sheffield Pulmonary Vascular Disease Unit and collected in the ASPIRE registry. Patients with suspected CTEPH undergo systematic evaluation but formal pulmonary angiography is only performed when other imaging modalities such as CTPA, MR imaging and nuclear medicine imaging are non-diagnostic. Results: 592 patients, mean age (± standard deviation), 65 ± 22 years, mean pulmonary arterial pressure 48 ± 13 mmHg and median pulmonary vascular resistance 480 ± 463 dynes/sec/cm -5 were identified and followed for 4.3 ± 3.2 years. 5 year survival was significantly (p < 0.001) better in CTEPH-surgical-operated (n = 279) at 82.9 ± 3.1% compared to CTEPH-surgical-not-operated (n = 206) at 44.4 ± 5% (66.7 ± 9.1% patient choice, 39.4 ± 6% comorbidities) and 53.4 ± 5.8% in CTEPH-non-surgical (n = 107). Only 4% of the patients in our study were investigated with conventional pulmonary angiography.The median time to PEA surgery from diagnosis was 10.2 months and did not affect long term survival (p = 0.52). Conclusions: For operable patients with CTEPH pulmonary endarterectomy is associated with an excellent long term outcome, the long-term survival of patients with surgical disease who decline surgery is significantly better than historically reported and that a non-invasive multimodality imaging approach can be used to assess patients with suspected CTEPH. Furthermore there is no time from diagnosis to surgery which predicts outcome.